The Mediating Role of Innovation Capability to Improve Knowledge Sharing on Smess Performancce - Faizzatur Rochma; Ayu Lucy Larassaty; Nafia Ilhama Qurratu’aini; Afifatus Sholikhah (Badan Penerbit STIEPARI Press, 2025)
This study aims to analyze the role of Knowledge sharing to improve SME Performance Small and Medium Enterprises (SMEs) in Sidoarjo by considering Innovation capability as a mediating variable. Using a quantitative method with an explanatory approach, data were collected from 31 respondents with a questionnaire and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The findings show that knowledge sharing has a significant influence on improving SME performance. However, innovation capability does not contribute directly to improving performance, but rather acts as a supporting factor in the continuous innovation process. The findings underscore the importance of building an effective knowledge sharing culture as a key strategy in enhancing SME competitiveness amidst evolving market dynamics.